Rent gap reloaded: Airbnb and the shift from residential to touristic rental housing in the Palma Old Quarter in Mallorca, Spain. (October 2019) - Yrigoy, Ismael
In light of the advent of Airbnb, rent gap theory can be helpful for understanding how tourist rentals affect residential rental housing. It is argued that on those properties currently rented to residents, rental payments are not only 'actual ground rent', but also 'potential ground rent'. The shift from a residential to a touristic use of rental housing thereby creates a potential ground rent. Taking as a case study the Palma Old Quarter in Mallorca, Spain, this paper analyses the evolution of the stock, prices, and revenues of residential rentals vis-à-vis tourist rentals and finds that, because it is more profitable to rent to tourists than to residents, the number of houses listed on Airbnb has increased, housing affordability for residents has shrunk, and the threat of displacement has increased.